Spatial-temporal analysis of the relationship between interprovincial migration and economic development in China: data from a bivariative autocorrelation study (2000 –2024) - Zhang, Feilong (Journal of the Belarusian State University. Economics, 2025)
Although interregional migration is a key factor in the development of China’s regional economies, existing studies often neglect its dynamic spatial dependence. This study quantitatively assesses the spatiotemporal relationship between interregional migration and economic development in 31 provinces of China from 2000 to 2024. By using bivariate spatial autoregressive analysis (global Moran’s I and local spatial autocorrelation index (LISA)) on provincial-level data from the National Bureau of Statistics of China, the impact of migration on GRP growth patterns is characterised. The results of the analysis allow us to identify three stages of regional agglomeration evolution: 1) the initial stage of extreme concentration of economic activity and migration flows in the eastern coastal regions (2000 –2009); 2) the phase of their partial rebalancing towards the western provinces (2010 –2019); 3) the final stage of policy-induced multipolar redistribution (2020 –2024). Different spatial regimes are also found, characterised by negative autocorrelation during the period of decentralisation (2005 –2014) and the emergence of clusters in new agglomeration hubs (2015 –2019).